Using functional groups to predict the spatial distribution of large herbivores on the Palaeo‐Agulhas Plain, South Africa, during the Last Glacial Maximum. (19th April 2022) - Brooke, Christopher F.; Marean, Curtis W.; Wren, Colin D.; Fritz, Hervé; Venter, Jan A.
ABSTRACT: Throughout much of the Quaternary, lower sea levels in the southern Cape of South Africa exposed a different landscape to what we see today, the Palaeo‐Agulhas Plain (PAP). The PAP was dominated by large‐bodied and gregarious grazing species contrasting with the small‐bodied predominantly solitary species we find in the region today. The distribution of these herbivores would likely have been driven by similar drivers we see in contemporary herbivore ecology. Importantly, the occurrence of early humans and their associated technology would have also influenced the probability of herbivores occurring in an area. Here we create a predictive model for large herbivores using probability of occurrence of functional grouping in relation to environmental drivers and humans. We show how early humans influenced the distribution of large herbivores on the PAP alongside other environmental drivers. In the fynbos biome, probability of occurrence was highest for the medium‐sized social mixed feeders' functional group in the thicket for small non‐social browsers, large browsers, and non‐ruminants and in grasslands for water‐dependent grazers. In our models, human influence affected functional groups to varying degrees but had the strongest effect on medium‐sized social mixed feeders.